Implementation of Web Service Security Using Oauth2 in the Financial Facility Search System - Maulana Zakaria, Danu; Fajar Kusumah, Fitrah Satrya (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
Implementation Of Web Service Security Using Oauth2 In Financial Facility Search System. The financial facility search system is an application that makes it easier for people to find the nearest financial facility. A similar application is Google maps which have been widely used to search for financial facilities, but for completeness of information and features, it is incomplete. So financial institutions need applications that can manage data on their financial facilities without other vendor intermediaries. This financial facility search system will be built on a mobile platform and website that is integrated with a web service. Financial facility data can be accessed publicly by the public so that the integrity of financial facility data needs to be maintained and secured from several threats that may occur. One such authentication process is the OAuth2 method. With the existence of OAuth2, this financial facility search system can overcome threats that may occur so that data integrity can be maintained.